Starten mit Spatz Kiko - Schwendimann, Maria; Bühler, Martina; Greber, Larissa; Lehnherr, Heidi; Trepp-Bühlmann, Seraina (Schwendimann, Maria Deutsch Eins., 2022)
Heft 1 deckt den Unterricht von August bis Dezember ab.